KEPASTIAN HUKUM DALAM MELAKSANAKAN PROSES PENDAFTARAN TANAH KETIKA MASA PANDEMI COVID-19 DI INDONESIA - Damianus Krismantoro (Jurnal Kelola: Jurnal Ilmu Sosial, 2020)
This study aims to examine whether the registration mechanism and procedure changed or not during the COVID-19 pandemic in Indonesia. The type of research used in this study is library research, namely research that uses written documents as data, and the data sources used in this study include primary legal materials, secondary legal materials and tertiary materials. Primary legal materials are legal materials that bind or make people obey the law, including legal products that are the subject of study and legal products as tools of criticism. The results of this study later found that during the COVID-19 pandemic, there was no new special process for land registration. During a pandemic, this process remains the same as before the pandemic. The problems in legal certainty have not changed in the field as a result of the obligation to follow health protocols.